Кон’юнктурний аналіз стратегії ціноутворення: мікроекономічний аспект - Кукіна, Наталя Володимирівна; Кукина, Наталья Владимировна; Kukina, Natalia; Васильченко, Олена Олегівна; Васильченко, Елена Олеговна; Vasylchenko, Olena (My University, 2018)
UK: У статті проведено аналіз попиту і пропозиції сільськогосподарської продукції аграрного підприємства та визначено основні тенденції формування ціни з урахуванням типу ринкової структури. Визначено напрями і заходи мікроекономічного характеру з удосконалення стратегії ціноутворення щодо підвищення економічних результатів сільськогосподарського виробництва. EN: The article analyzes the demand and supply of agricultural products of agrarian enterprises and outlines the main tendencies of price formation taking into account the type of market structure. The directions and measures of the microeconomic nature of improving the pricing strategy for increasing the economic results of agricultural production are determined. The purpose of the article is to substantiate theoretical and methodological principles and promising practical directions of improving the pricing strategy in agricultural enterprises on the basis of microeconomic analysis. The methodological and organizational-economic issues related to the scientifically grounded pricing formation on the principles of improving the pricing strategy by the limit indicators of production, the formation of economically justified demand differentiation, and the identification of the nature of price elasticity for agricultural enterprises are disclosed. In other words, the microeconomic aspect of choosing a pricing strategy is investigated.
Conjunctional analysis of pricing strategy: microeconomic aspects
Keywords: ціна; витрати; прибуток; ринкова структура; рівень рентабельності; коефіцієнт еластичності; диференціювання цін; price; cost; profit; market structure; profitability level; coefficient of elasticity; price differentiation